Chronic, Refractory CRPS Involving 3 Limbs: A Case Report - Zyluk, A. (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2013)
We report the case of a 26-year-old woman with CRPS involving consecutively 3 extremities during 8 years. None of the treatments used was effective and each CRPS episode resulted in persistence and chronification of the disease. We suggest that this patient presents a specific subtype of the disease, called “chronic, refractory CRPS” which is extremely severe, disabling and resistant to treatment.
Keywords: CRPS; pain; classification; complex regional pain syndrome; contracture